A Robust Immersed Boundary-Lattice Boltzmann Method for Simulation of Fluid-Structure Interaction Problems (Communications in Computational Physics, 2018)
A robust immersed boundary-lattice Boltzmann method (IB-LBM) is proposedto simulate fluid-structure interaction (FSI) problems in this work. Comparedwith the conventional IB-LBM, the current method employs the fractional step techniqueto solve the lattice Boltzmann equation (LBE) with a forcing term. Consequently,the non-physical oscillation of body force calculation, which is frequently encounteredin the traditional IB-LBM, is suppressed greatly. It is of importance for the simulationof FSI problems. In the meanwhile, the no-slip boundary condition is strictly satisfiedby using the velocity correction scheme. Moreover, based on the relationship betweenthe velocity correction and forcing term, the boundary force can be calculated accuratelyand easily. A few test cases are first performed to validate the current method.Subsequently, a series of FSI problems, including the vortex-induced vibration of a circularcylinder, an elastic filament flapping in the wake of a fixed cylinder and sedimentationof particles, are simulated. Based on the good agreement between the currentresults and those in the literature, it is demonstrated that the proposed IB-LBM has thecapability to handle various FSI problems effectively.